GLP-1 receptor agonists in Alzheimer’s and Parkinson’s disease: endocrine pathways, clinical evidence, and future directions - Gandhi, Ayush; Parhizgar, Alireza (Frontiers in Endocrinology, 2025)
Initially developed for type 2 diabetes and obesity, glucagon-like peptide-1 receptor agonists (GLP-1RAs) are now emerging as promising candidates for modifying the course of neurodegenerative diseases. This potential stems from the presence of GLP-1 and its receptors within the central nervous system (CNS), where their signaling activity influences critical processes like synaptic plasticity, neuroinflammation, insulin signaling, and cellular energy management. In fact, preclinical models of both Alzheimer’s disease (AD) and Parkinson’s disease (PD) have shown that GLP-1RAs can reduce neuroinflammation, improve mitochondrial function, and enhance the clearance of toxic proteins (proteostasis), leading to benefits in cognition and the survival of dopaminergic neurons. Yet, when tested in humans, the picture has been more nuanced and less straightforward. Early clinical trials in AD have produced mixed cognitive signals, though they have shown intriguing biological effects, such as preserved cerebral glucose metabolism with liraglutide on FDG-PET scans. In contrast, the evidence in PD has been more consistent, with agents like exenatide and lixisenatide demonstrating motor benefits, although one trial with a pegylated exendin (NLY01) did not meet its primary endpoint. The definitive test will come from large, ongoing phase 3 programs, such as the EVOKE and EVOKE+ trials for semaglutide. Should these trials are successful, GLP-1RAs could become a cornerstone of earlier, mechanism-based intervention strategies for neurodegenerative diseases.